1995
DOI: 10.1007/bf00373914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ?-guanidinopropionic acid-feeding on the patterns of myosin isoforms in rat fast-twitch muscle

Abstract: Administration of beta-guanidinopropionic acid (beta-GPA) to rats as 1% of their diet for 6 weeks led to an accumulation of beta-GPA and beta-GPA-phosphate and to a depletion of creatine and phosphocreatine in the fast-twitch plantaris muscle. Adenosine triphosphate concentration was also decreased. Electrophoretic analyses were performed to investigate the effects of beta-GPA on the patterns of fast (FM) and slow (SM) isomyosins, myosin heavy chain (HC) isoforms and myosin light chain (LC) isoforms. The relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
4
20
1
Order By: Relevance
“…The exact mechanisms underlying fiber-type transitions remain to be elucidated and the control of the expression of genes encoding contractile and metabolic proteins has not been clearly identified to date. Previous studies showed that chronic administration of ␤-guanidinopropionic acid, a chemical that decreases the PCr/ATP ratio in muscle, induced a switch from fast to slow myosin isoforms (30). The results of the present study are in accordance with these findings and suggest that the energy potential of muscle fibers could play a regulatory role in determining the muscle phenotype (31).…”
Section: Discussionsupporting
confidence: 91%
“…The exact mechanisms underlying fiber-type transitions remain to be elucidated and the control of the expression of genes encoding contractile and metabolic proteins has not been clearly identified to date. Previous studies showed that chronic administration of ␤-guanidinopropionic acid, a chemical that decreases the PCr/ATP ratio in muscle, induced a switch from fast to slow myosin isoforms (30). The results of the present study are in accordance with these findings and suggest that the energy potential of muscle fibers could play a regulatory role in determining the muscle phenotype (31).…”
Section: Discussionsupporting
confidence: 91%
“…muscles of ␤-GPA-fed rats were lower than in the control rats, as reported previously [6,[10][11][14][15][16][17][18]. In contrast, high-energy phosphate levels were elevated in the creatine-fed group.…”
Section: Discussionsupporting
confidence: 84%
“…In this context, it is also of interest that fast-to-slow transitions in myosin expression have been observed in Cr-depleted fast-twitch muscles of mouse [16] and rat [1,22]. Under these conditions, where the metabolic state of the muscle was directly manipulated, myosin light and heavy chain expression were found to be shifted towards slower isoforms.…”
Section: Discussionmentioning
confidence: 93%